HUBUNGAN PENGARUH PROMOSI KESEHATAN DENGAN (MEDIA POSTER) TERHADAP PENGETAHUAN BAHAYA MEROKOK DI DALAM RUMAH DI DESA LUT KUCAK KECAMATAN WIH PESAM KABUPATEN BENER MERIAH - Dilla Novianita; Muzaffar; Saipullah (Jurnal Ilmiah Cerebral Medika, 2026)
ABSTRACT Clean and Healthy Living Behavior (PHBS) is essentially the basis for preventing humans from various diseases. Cigarettes are one of the biggest causes of preventable death in society. The consequences that can be caused are not only for smokers themselves (active smokers) but also for people who inhale the smoke, called passive smokers. In addition to having an impact on health problems, smoking can also have an impact on social, economic and environmental issues. To determine the effect of health promotion with poster media on knowledge of the dangers of smoking in the home in Lut Kucak Village, Wih Pesam District. The research design used was a quasi-experimental with a pretest and posttest one group method without a control group that describes the effect of health promotion with poster media on knowledge of the dangers of smoking in the home in Lut Kucak Village. The study was conducted in Lut Kucak Village, Wih Pesam District. The level of knowledge of the good category of respondents before health promotion with posters was 8.3% and after health promotion using posters increased by 77.8% while the level of knowledge of respondents in the poor category before health promotion with posters was 63.9% and after being given health promotion using poster media decreased to 6.3% based on the results of the study showed that there was a significant influence between the knowledge of respondents (heads of families) about the dangers of smoking in the house given poster media with the knowledge of respondents (heads of families) after being given poster media. To the Health Center to carry out monitoring and promotion with poster media so that it is easy to understand about health regarding the dangers of smoking in the house in Lut Kucak Village. Keywords : Knowledge, Smoking in the house